Hilangnya Kesadaran Diri Mahasiswa untuk Kuliah - Katharina Woli Namang; Maria Eka Febriyani Dua Dala (Jurnal Pustaka Cendekia Pendidikan, 2025)
The loss of students' self-awareness to go to college is a phenomenon that is carried over into the world of higher education. This phenomenon reflects the phenomenon of motivation, enthusiasm for learning, and responsibility for academic tasks that should be a priority. The purpose of this study is to increase students' self-awareness of the importance of college. This study uses a quantitative method. In this study, researchers describe objectively the loss of students' awareness in college. The data selected are direct communication and data sources obtained through PBSI Semester 1 students of Muhammadiyah University of Maumere. The results of the study indicate that by increasing access and quality of education and building public awareness, this problem can be overcome. In addition, increasing awareness of the importance of education can be done by building an active and supportive learning community. This can be achieved by holding discussions and other activities that promote the importance of education.